The United Nations convention on the rights of persons with disabilities (UNCRPD) and Malaysia: an overview - Md. Tah, Ikmal Hisham; Mokhtar, Khairil Azmin (Zes Rokman Resources, 2016)
Marginalization and discrimination of Persons with Disabilities (PWD) by a certain segment of societies are common problems in many countries mainly due to lack of legal measures in addressing the problems. This is one of the main factors that leads to the creation by the UN of the Convention on the Rights of Persons with Disabilities and the Optional Protocol (UN CRPD) in 2006. The treaty is significant due to various reasons one of them is because it shifts the promotion and protection of the rights of people with disabilities from medical or charity model towards social model which concentrates on human rights based approach. This approach has become recent phenomena in international law which have been adopted by jurisdictions all over the world. In order to fulfill its international obligation in this regards Malaysia had become a signatory of the UN CRPD in 2008 and later ratified it in 2010. The commitment became the impetus for the enactment of the PWD Act 2008. Malaysia, however, has made reservations on two main articles of the CRPD namely Article 15 (freedom of torture or cruel, inhuman or degrading treatment or punishment) and Article 18 (liberty of movement and nationality). It also does not sign the Optional Protocol which allows individual and groups complaint to the CRPD Committee for any breach occurred. This paper will analyze the Malaysian’s compliance with the UN CRPD. It is concluded that the reservation of the articles should be removed and interpretative declaration should be made to ensure it is in accordance with Federal Constitution and domestic laws in Malaysia.